Evaluasi Pelaksanaan dan Strategi Keberlanjutan Program Padat Karya Pangan di Kabupaten Timor Tengah Utara - Kurniawati Dima, Yuliana (Jurnal Ilmiah Administrasi Publik, 2016)
This paper aims to evaluate Food Intensification Program and to examinesustainable strategic of this program in Timor Tengah Utara Regency. This study used mixed methods approach, exploratoy sequential, data come from inteview and the result used for collecting quantitative data with A’WOT method. The results show that the implementation of this program has not been strictly driven as be planned. This caused by several reasons. The prioritized strategy, result from A’WOT analysis is increasing the intensity of counseling and formation of farmer groups for the improvement of farmers' resources. This study recommends several important points, such follow: (1) theory of planning and theory ini planning needed to improve effective plannings, (2) To provide intensive assistances, by increasing the capacity of field assistances, in order to change the behavior of farming communities.